The Perception of Muslim Travellers of TheSupporting Facilities of Halal Tourismin Kota Kuala Lumpur Malaysia - Septiana, Khoirun Najmi; Mohamad, Nur Azreen Binti (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this study was to analyze the perception of tourist muslin on infrastructure facilities to support halal tourism in Malaysia. The type of research used is qualitative descriptive research, with accidental sampling techniques, where the sample is Muslim tourists who were met at the time of the research. Data collection techniques used are interviews and documentation, then the data obtained are analyzed using descriptive methods to present the facts encountered during the research process. The results show that in terms of facilities, such as transportation, accommodation, food, places of worship are very easy to reach and support the implementation of halal tourism. In terms of supporting infrastructure has also been very good, seen from the smooth flow of transportation and communication for Muslim tourists in the city of Kuala Lumpur, Malaysia. So, the perception of Muslim tourists on the facilities for supporting halal tourism in the City of Kuala Lumpur, Malaysia has been very good and in accordance with the standard facilities for supporting halal tourism infrastructure, as well as increasing tourists' insight into Islamic culture in Southeast Asia.